The Effect of Incorporation of Polyethylene and Glass Fiber on the Microleakage of Silorane-based and Methacrylate-based Composites in Class II Restorations: An in Vitro Study - Sharafeddin F; Darvishi F; Malekzadeh P (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Microleakage is one of the most important problems in composite restorations. One way to reduce the microleakage is decreasing the total amount of resin by insertion of fibers in composite restorations. Objectives: This study aimed to compare the microleakage of Silorane and methacrylate-based composites (a nanohybrid) in Class II restorations with gingival margins on the root surface, with or without placing glass and polyethylene fiber. Materials and Methods: 60 extracted sound third mandibular molars were disinfected. Class II slot cavities were provided on both proximal sides of each tooth. Based on application of composites and fibers, the teeth were randomly divided into 6 groups (n=20). group1: Z350; group2: Z350 + polyethylene fiber; group3: Z350 + glass fiber; group4: P90; group5: P90 + polyethylene fiber; and group6: P90 + glass fiber. The specimens were thermocycled, immersed in 2% basic fuchsine dye solution, and then sectioned to assess dye penetration under stereomicroscope (40X). Results were statically analyzed by Kruskal-Wallis and Mann-Witney tests at a significance level of p<0.05. Results: There was a significant decrease in microleakage in Silorane composite when compared to nanohybrid composite (p<0.001). There was not any significant difference among groups with or without fiber inserts. Conclusions: The use of Silorane composite reduces the microleakage in comparison with nanohybrid composite and fiber insertion had no effect on the microleakage in class II silorane and nanohybrid composite restorations with gingival margins below the CEJ.